2016
DOI: 10.1074/jbc.m116.746289
|View full text |Cite
|
Sign up to set email alerts
|

EspR-dependent ESAT-6 Protein Secretion of Mycobacterium tuberculosis Requires the Presence of Virulence Regulator PhoP

Abstract: Attenuation of Mycobacterium bovis BCG strain is related to the loss of the RD1-encoded ESX-1 secretion system. The ESX-1 system secretes virulence factor ESAT-6 that plays a critical role in modulation of the host immune system, which is essential for establishment of a productive infection. Previous studies suggest that among the reasons for attenuation of Mycobacterium tuberculosis H37Ra is a mutation in the phoP gene that interferes with the ESX-1 secretion system and inhibits secretion of ESAT-6. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 61 publications
(54 reference statements)
2
43
1
Order By: Relevance
“…Considering the above results, recently-reported PhoP-DosR interaction (23) emerged as a possible explanation to account for the regulation of hypoxia-inducible genes. To examine this, whole cell lysate of ΔphoP expressing His-tagged PhoP, as described previously (35), was incubated with Ni-NTA, and proteins were eluted from Ni-NTA column using imidazole (Fig. 4B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the above results, recently-reported PhoP-DosR interaction (23) emerged as a possible explanation to account for the regulation of hypoxia-inducible genes. To examine this, whole cell lysate of ΔphoP expressing His-tagged PhoP, as described previously (35), was incubated with Ni-NTA, and proteins were eluted from Ni-NTA column using imidazole (Fig. 4B).…”
Section: Resultsmentioning
confidence: 99%
“…While these results suggest convergence of two different types of signalling modules for a common function, along the similar line DosR interacts with the house keeping sigma factor SigA for bacterial survival under dormancy (17). Recently, we have shown that PhoP interacts with nucleoid-associated protein EspR to control ESAT-6 secretion (35). In this study, we show that N-domains which get phosphorylated for activation of respective regulators, interact to each other (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PhoP is part of a two-component system that regulates several virulence pathways in M. tuberculosis, including biosynthetic genes of the M. tuberculosis-specific lipids, sulfolipid, DAT, and PAT (103). In addition to regulating lipid biosynthesis genes, PhoP also regulates whiB6 and works directly with EspR, and both regulate ESX-1 gene expression (96,104,105). Therefore, under many of the conditions in which cell envelope remodeling may be occurring or where cell wall genes are regulated, ESX genes are also regulated.…”
Section: Cell Wall Synthesis and Esx Systemsmentioning
confidence: 99%
“…Alternatively, the ESX substrates may direct their own transit across the MOM, by either forming the apparatus spanning the MOM or by transiting the MOM directly (48,104,(157)(158)(159). Notably, the EspC substrate of the ESX-1 system in M. tuberculosis (160) was recently reported by Lou et al to self-assemble into filaments in vitro.…”
Section: Crossing the Envelopementioning
confidence: 99%
“…phoP deletion mutants of M. tuberculosis are attenuated for growth in THP‐1 macrophages as well as in murine bone marrow‐derived macrophages . PhoP/PhoR regulates espB and espR which are essential for ESX‐1 mediated secretion of ESAT‐6. In a recent study, it has been demonstrated that PhoP and EspR interact directly with each other and are recruited to the espACD promoter.…”
Section: Introductionmentioning
confidence: 99%